Actualizing Qur'anic Sadaqah: Jimpitan as Lived Islamic Practice in Rural Indonesia - Putri Guspida; Pathur Rahman; Ahmad Syarif Hidayatullah (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
This ethnographic study examines how rural Indonesian Muslims actualize Qur’anic teachings on charity (sadaqah) through jimpitan, a longstanding practice of nightly rice collection in Dusun II, Rejodadi Village, Sembawa, Banyuasin, South Sumatra. Rather than treating this tradition merely as cultural heritage, this research interprets it as lived Islam, specifically as an ongoing enactment of sadaqah jariyah (continuous charity) grounded in Q.S. Al-Baqarah: 274. Drawing on six months of participant observation and in-depth interviews with religious leaders, hamlet officials, jimpitan organizers, and community members, the analysis reveals how this practice embeds Islamic principles of ikhlas (sincerity), gotong royong (mutual cooperation), and social empathy in the daily rhythms of community life. Beyond its economic role in allocating auctioned rice revenues for communal benefit, jimpitan strengthens social bonds, reinforces collective responsibility, and enhances participation in local security patrols. What emerges is not simply philanthropic behavior but a distinctive mode of religious interpretation—one that translates Qur’anic values into culturally resonant forms without necessarily invoking explicit textual references. By employing a Living Qur’an framework, this research demonstrates how scriptural ethics become embedded in social practice, offering insights into the dynamic relationship between Islamic teachings and rural Muslim life in contemporary Indonesia.